The Effect of the Developed Differentiation Approach on the Achievements of the Students - ÖZDEMİR, AHMET ŞÜKRÜ (ANI YAYINCILIK, 2015)
Problem Statement: The present study is of importance for designing a differentiation approach, which enables gifted students to use their present potential in mathematics effectively and enables them to develop their achievement, while looking at the effect of the approach on both gifted and non-gifted students. Within the scope of the developed differentiation approach concerning mathematics education of gifted students, the present study is one of the limited studies with such a focus, which is why it is thought that it will contribute to the literature. By the results of the study, it is of great importance. Purpose of the Study: The purpose of this research is to determine the effect of a newly-developed differentiation approach for the mathematics education of gifted middle school students on the achievements of both gifted and non-gifted students. Method: Within the scope of this current study, the model with pre-test and post-test control group among real research models in accordance with quantitative research method was used. The sample of the study was composed of 57 gifted and 60 non-gifted 5th and 6th grade students from a public school and a private school in Maltepe and Cekmekoy districts of Istanbul. Convenience and purposeful sampling were conducted within the scope of quantitative sampling in this study. 'Mathematics Achievement Test' and 'Multiple-Intelligences Domains Inventory' were used within the scope of this study. The lessons carried out using activities stated in the National Education curriculum about the related subjects were compared with lessons carried out with the activities designed according to the differentiation approach developed in three implementations conducted. Findings: The research made in private school showed that there is a significant difference between current-enriched and overall scores of gifted students in control and experimental groups after the application on behalf of the experimental group. The research made in the state school showed that there is a significant difference between current-enriched and overall scores of non-gifted students in control and experimental groups after the application on behalf of the experimental group. Conclusion and Recommendations: There was a significant increase in the achievement scores of experimental group students, where the activities designed according to differentiation approach developed within the scope of this study, when compared with the control group students during all of the implementations. This situation shows that activities and curriculum differentiation studies, which are based on elaboration, creative thinking, and multiple intelligences increase students' academic achievements. Besides, it is seen that the changes based on creativity strategies on the content, process, product, and learning environments increase students' academic achievements. The effectiveness of the developed differentiation approach should be researched with different grade levels, on different topics. It is suggested to use developed differentiation approach periodically for teachers and students to gain experience. It is further suggested to inform generally all teachers across the country about how they will guide the process of preparing projects and for teachers to inform their students about how they will prepare projects.
Keywords: Giftedness; teaching mathematics; differentiation; multiple intelligence